A Phase I, Open-Label, Multicenter, Dose-escalation Study of the Oral Selective FGFR Inhibitor Debio 1347 in Patients with Advanced Solid Tumors Harboring FGFR Gene Alterations - Voss, Martin H; Hierro, Cinta; Heist, Rebecca S; Cleary, James M; Meric-Bernstam, Funda; Tabernero, Josep; Janku, Filip; Gandhi, Leena; Iafrate, A John; Borger, Darrell R; Ishii, Nobuya; Hu, Youyou; et al. (Clinical cancer research, 2019)
To investigate tolerability, efficacy, and pharmacokinetics/pharmacodynamics of Debio 1347, a selective FGFR inhibitor. This was a first-in-human, multicenter, open-label study in patients with advanced solid tumors harboring gene alterations. Eligible patients received oral Debio 1347 at escalating doses once daily until disease progression or intolerable toxicity. Dose-limiting toxicities (DLT) were evaluated during the first 4 weeks on treatment, pharmacokinetics/pharmacodynamics postfirst dose and after 4 weeks. A total of 71 patients were screened and 58 treated with Debio 1347 at doses from 10 to 150 mg/day. Predominant tumor types were breast and biliary duct cancer, most common gene alterations were amplifications (40%) and mutations in (12%) and (17%); 12 patients (21%) showed fusions. Five patients at three dose levels had six DLTs (dry mouth/eyes, hyperamylasemia, hypercalcemia, hyperbilirubinemia, hyperphosphatemia, and stomatitis). The maximum tolerated dose was not reached, but dermatologic toxicity became sometimes dose limiting beyond the DLT period at ≥80 mg/day. Adverse events required dose modifications in 52% of patients, mostly due to dose-dependent, asymptomatic hyperphosphatemia (22%). RECIST responses were seen across tumor types and mechanisms of FGFR activation. Six patients, 3 with fusions, demonstrated partial responses, 10 additional patients' tumor size regressions of ≤30%. Plasma half-life was 11.5 hours. Serum phosphate increased with Debio 1347 plasma levels and confirmed target engagement at doses ≥60 mg/day. Preliminary efficacy was encouraging and tolerability acceptable up to 80 mg/day, which is now used in an extension part of the study.